Biogeochemical processes in a tropical hypersaline lagoon: trophic crises, diffusive fluxes, and phytoplankton nutrition - Trevisan, Cleuza Leatriz (2024)
Coastal lagoons are among the most productive ecosystems in the world, but they have been severely impacted by cultural eutrophication, which affect both the ecosystem and the local community. Nutrients (nitrogen and phosphorus) that reach the lagoons can have different destinations. Part of nutrients is used by autotrophic organisms, another fraction remains in the water, or is deposited and accumulated in the sediment through diagenetic processes. At the sediment–water interface, chemical interactions can remobilize nutrients to the water column, alter existing chemical species, or form new compounds. Nutrient fluxes can favor an unbalanced increase in phytoplankton biomass and reduce water transparency by promoting the maintenance of primary productivity. The Laguna de Araruama (AL) is a coastal lagoon of great ecological and social relevance in the Região dos Lagos (Rio de Janeiro). However, anthropogenic changes since the 1970s have impacted this ecosystem, with the establishment of eutrophic conditions in 2005 and the occurrence of fish mortality and HAB since then. The present work was motivated by episodes of change in water transparency occurred between 2019 and 2022. The methodology comprised three different approaches, each one linked to a specific objective, forming the main axis of the thesis: 1) trophic crises and their causes; 2) quantification of nutrient fluxes; and 3) the nutritional requirements of local phytoplankton. Samples of water, sediment, and phytoplankton were collected in 9 campaigns between 2019 and 2022, and an equipment was developed to filtrate different sizes of phytoplankton. The Araruama Lagoon was compartmentalized into three sectors according to the salinity gradient from the sea connection to western portion: marine (32-35); central (50-67); and interior (35-50). The pore water presented very high nutrient contents, in some cases up to 100 times higher than the overlying water at the water–sediment interface. The direct indicators of trophic crises were phosphate, ammonium, and nitrite+nitrate and the N:P ratio favored by the diffusive fluxes of phosphorus and nitrogen. While the indirect descriptors were temperature, salinity, and turbidity. The turbid water (maximum Secchi =1.0 m) showed fluxes between 0.08–2.7 μmol L–1 (phosphate), 0.17–65 μmol L–1 (ammonium), and 15.6–70.3 μmol L–1 (nitrite+nitrate) and N:P ratio between 7–330. Non–turbid water (maximum Secchi =3.8 m) ranged from 0.08–1.3 μmol L–1 (phosphate), 0.17–9 μmol L–1 (ammonium), and 1.5–18 μmol L–1 (nitrite+nitrate). To complete, a mass balance determined the nutritional requirements of local phytoplankton (cyanobacteria, dinoflagellates, and diatoms) at 32.76 μg N g–1 and 26.66 μg P g–1 . The results indicated that sediments and sewage are the sources of nutrients for the maintenance of local phytoplankton, and that they can accentuate the critical state of the lagoon. Affirmative and effective environmental management actions are necessary to reduce future negative impacts on this unique environment.